Clinical and Pathological Spectrum of Wilson Disease in Children at a Tertiary Care Hospital of Faisalabad, Pakistan: Clinical and Pathological Spectrum of Wilson Disease in Children - Shahzadi, Nagina; Bilal, Hazrat; Malik, Hassan Suleman; Batool, Zahra; Aslam, Irum; Munir, Kalsoom (Pakistan Journal of Health Sciences, 2025)
Wilson disease is a genetic disorder related to copper metabolism that follows an autosomal recessive pattern. Objectives: To document the clinical and pathological spectrum of Wilson disease at a tertiary setting in Punjab, Pakistan. Methods: This cross-sectional study was conducted at the Department of Pediatric Gastroenterology, Children's Hospital, Faisalabad, Pakistan, from December 2019 to October 2024. A total of 60 children of both genders aged below 18 years, and presenting with Wilson disease were analyzed. Physical and clinical examinations were performed and medical history was taken in all Wilson disease cases. Demographic and clinical characteristics were noted, and relevant laboratory investigations were done. Results: In a total of 60 children with Wilson disease, 42 (70.0%) were boys. The mean age was 10.25 ± 3.10 years. The most frequent signs and symptoms were Jaundice, hepatomegaly, ascites, and coagulopathy, noted in 53 (88.3%), 41 (68.3%), 36 (60.0%), and 24 (45.0%) children respectively. Kaiser Fischer ring was noted in 16 (26.7%) children. The mean Wilsons index score was 9.77 ± 2.98 while 31 (51.7%) children had scores ≥10. The mean ceruloplasmin and 24-hour urinary copper levels were 7.03 ± 7.51 mg/dl and 746.03 ± 451.06 µg. Conclusions: It was concluded that hepatic manifestations are the most common among children with Wilson disease. The most frequent signs and symptoms among children were Jaundice, hepatomegaly, and ascites. There is a need to identify factors that contribute to early diagnosis and prompt treatment, thereby preventing severe brain damage and liver failures in affected patients.